Availability of fish catch production yellowfin tuna (Thunnus albacares) landed in the Bungus Ocean Fishery Port of West Sumatra Province - Arthur Brown; Purwati Purwati; Isnaniah Isnaniah (Science, Technology, and Education Care, 2023)
This research aims to determine predictions of yellowfin tuna catch production and conditions of catch production in 2021-2025 and the factors influencing yellowfin tuna catches. This research was conducted in September 2021 at the Bungus Marine Fisheries Harbor. The data taken is primary and secondary. The analysis used is Catch Production Projection Analysis and quadratic (Polynomial) Regression Analysis. The research results show that in catch projections, there is data on fish catch production for 2021-2025, where predictions for the next five years will fluctuate, or yellowfin tuna production will increase yearly. In the results of quadratic (polynomial) regression research, the factors that most influence the output of yellowfin tuna catches using quadratic regression are the number of fishing gear with a coefficient of determination or R2 value of 0.9934 and the number of fishermen with a coefficient of determination or R2 value of 0. 9934. The coefficient of determination or R2 value is 0.9599